Effects of high glucose concentrations on the endothelial function of the renal microcirculation of rabbits - Affonso,Filipe de Souza (2003)
OBJECTIVE: To assess the acute effects of high glucose concentrations on vascular reactivity in the isolated non diabetic rabbit kidney. METHODS: Rabbits were anaesthetized for isolation of the kidneys. Renal arteries and veins were cannulated for perfusion with Krebs-Henselleit solution and measurement of perfusion pressure. After 3 hours of perfusion with glucose 5,5 mM (control ) and 15 mM, the circulation was submitted to sub maximal precontraction (80% of maximal response) trough continuous infusion of noradrenaline 10 mM. Vascular reactivity was then assessed trough dose-responses curves with endothelium-dependent (acetylcholine) and independent (sodium nitroprusside) vasodilators. The influence of hyperosmolarity was analyzed with perfusion with mannitol 15mM. RESULTS: A significant reduction in the endothelium-dependent vasodilation in glucose 15mM group was observed compared to that in control, but there was no difference in endothelium-independent vasodilation. After perfusion with mannitol 15 mM, a less expressive reduction in endothelium-dependent vasodilation was observed, only reaching significance in regard to the greatest dose of acetylcholine. CONCLUSION: High levels of glucose similar to those found in diabetic patients in the postprandial period can cause significant acute changes in renal vascular reactivity rabbits. In diabetic patients these effects may also occur and contribute to diabetes vascular disease.